Helminthiasis in the pigs of rangamati district of bangladesh - Safiul Ahad Sardar; Debaraj Chakma; Anisuzzaman; Kamal Hossain; Ausraful Islam (Eurasian Journal of Veterinary Sciences)
This study was conducted to determine the prevalence of helminths among domestic pigs. Totally 135 local pigs and cross-breed pigs were sampled. The faecal samples were examined by using Stoll`s ova counting method. Among the sampled pigs 75 (55.5%) were infected with one or more species of helminths. The prevalence of Metastrongylus sp. and Fasciolopsis sp. was significantly (p<0.05) higher in the pigs of 0-12 months age and 0-70 kg body weight groups compared to over 12 months and 70 kg body weight groups. The prevalence of Fasciolopsis sp. was significantly (p<0.05) higher in males and local pigs than females and cross-breed pigs, respectively. In conclusion, pigs are infected with several species of helminths. So regular dewarming is necessary which will not only develop the health status of the domestic pigs but also will reduce the risk of the zoonoses.